Mother Tongue Interference Patterns in Arabic Student Writing: Polanya Gangguan Bahasa Ibu dalam Penulisan Siswa Arab - Shafa Salsabila; Moch. Bahak Udin By Arifin (Universitas Muhammadiyah Sidoarjo, 2025)
eneral Background: Writing skills constitute a core component of Arabic language mastery and require accuracy in lexical choice, grammatical structure, and morphological formation. Specific Background: In second language acquisition, mother tongue interference frequently occurs when learners transfer linguistic patterns from their first language into the target language. Knowledge Gap: Previous studies on interference in Arabic learning have predominantly focused on spoken data, leaving limited analysis of interference patterns in written Arabic among university students. Aims: This study aims to analyze the forms and impacts of mother tongue interference on the Arabic writing ability of fourth-semester students in the Arabic Language Education Study Program at the University of Muhammadiyah Malang. Results: Using a qualitative case study approach and content analysis, the findings reveal five categories of interference: lexical (4 cases), grammatical (4 cases), morphological (12 cases), semantic (8 cases), and orthographic (2 cases), with morphological errors being the most dominant. These interferences lead to structural deviations, inaccurate diction, and shifts in sentence meaning. Novelty: This study provides a comprehensive classification of written interference forms based on authentic student assignments within a higher education context. Implications: The results indicate the necessity of structured kitabah practice, reinforcement of nahwu and sharaf rules, and habituation to thinking directly in Arabic to improve writing quality. Keywords: Mother Tongue Interference, Arabic Writing Skills, Qualitative Case Study, Content Analysis, Second Language Acquisition Key Findings Highlights: Morphological deviations constituted the highest frequency of errors. Structural transfer from Indonesian altered sentence construction patterns. Meaning shifts occurred due to incorrect verb forms and lexical selection.